Utility of Boenninghausen’s Characteristics and Repertory in Management of the Cases of Rheumatoid Arthritis An Observational Study (Advancements in Homeopathic Research, 2023)
Background: Rheumatoid arthritis (RA), an  autoimmune, progressive, inflammatory condition  affects daily activities, psychosocial life of patient.  Homoeopathic constitutional similimum improves  quality of life by reducing intensity of pain,  limiting disability and reducing disease activity.  Cyrus Maxwell Boger introduced the concept of  pathological generals, time modalities and tissue  affinities in “Boenninghausen’s Characteristic &  Repertory (BCR)”.Objective: To assess effectiveness of homoeopathic  medicines selected with the aid of BCR by C.M. Boger  in management of the cases of RA by comparing pre and post-treatment changes in Disease Activity Score  28 (DAS28).Method: It was a 9-month observational study  conducted on 50 patients diagnosed with RA using  American Classified Revised (ACR) diagnostic  criteria and by laboratory investigations. DAS28 used  for pre- and post- treatment evaluation, paired t test  for statistical analysis and homoeopathic medicines  were given after repertorising with the help of BCR. Results: Forty one patients completed the study,  which showed that females were more prone, most  affected age group was 46-50 years. Commonly  affected joints were wrist joints. Common  aggravating time was morning, presented without any  past history, deformity, family history. Commonly  prescribed medicines were Sepia officinalis and  Calcarea carbonica. Mean of DAS28 score showed  improvement after the treatment. Paired t test showed  significant results (t = 9.931, p =0.001). Conclusion: The findings showed 87.8% of cases  responded with mild relief in their symptoms to the  indicated homoeopathic medicines selected with the  aid of BCR. Hence, proved the significant utility of  BCR in management of RA.
Keywords: Rheumatoid arthritis; Boenninghausen’s Characteristics & Repertory; Disease Activity28 Score (DAS28 Score); Homoeopathy